Prophylaxis of Macular Edema with Peroperative Intravitreal Bevacizumab in Patients with Diabetic Retinopathy Undergoing Phacoemulsification - Ali Raza, Sidra Jabeen, Rizwan Khan (Pakistan Journal of Ophthalmology, 2019)
Purpose: To determine frequency of post-operative macular edema in patients with diabetic retinopathy receiving peroperative Intravitreal bevacizumab, as compared to controls after phacoemulsification cataract surgery. Study Design: Randomized control trial. Place and Duration of Study: Ophthalmology department holy family hospital Rawalpindi from July, 2016 to January, 2017. Materials and Methods: 60 patients who reported at the health care facility with diabetic retinopathy were included in the study. Out of these 30 were kept as control and 30 as cases. Data was collected and entered into SPSS version 19.0. Numerical variables were accounted for as mean and standard deviation whereas qualitative variables were accounted for as frequency and percentages. To compare the occurrence of macular edema at completion of 6 weeks in both study groups, Pearson’s chi-square test at 5% level of significance was applied. A p- value of 0.05 was considered as statistically significant. To control effect modifier by gender, and age, stratified analysis was also executed. Results: The participants of the study had mean age of 61.97 ± 5.7 years. Out of the 60 patients 33 (55%) were female. Analysis of both groups showed that macular edema was found in 4 (13.33%) patients in control group and 17 (56.67%) patients in group B. Most significant macular edema was seen in 11 patients in age group of 61-70 years. Gender wise stratification showed that 9 (56.5%) female patients reported with macular edema. Conclusion: Peroperative intravitreal bevacizumab is effective in prophylaxis of macular edema in patients with mild to moderate NPDR, as compared to controls, Keywords: NPDR, Intravitreal bevacizumab, Diabetic Retinopathy, Macular edema, Phacemulsification surgery.